The social contract in Africa - Osha, Sanya (Africa Institute of South Africa, 2014)
This book employs the event of the Arab Spring revolution of 2011 to reflect on the event itself and beyond. Some of the chapters address the colonial encounter and its lingering reverberations on the African sociopolitical landscape. Others address the aftermath of large scale societal violence and trauma that pervade the African context. The contributions indicate the range of challenges confronting African societies in the postmodern era. They also illustrate the sheer resilience and inventiveness of those societies in the face of apparently overwhelming odds. What is the nature of politica.